HE4 and CA125 levels in the preoperative assessment of endometrial cancer patients: a prospective multicenter study (ENDOMET). (14th October 2013) - Antonsen, Sofie L.; Høgdall, Estrid; Christensen, Ib J.; Lydolph, Magnus; Tabor, Ann; Loft Jakobsen, Annika; Fagö‐Olsen, Carsten L.; Andersen, Erik S.; Jochumsen, Kirsten; Høgdall, Claus
Abstract Objective To evaluate whether human epididymis protein 4 (HE4) and CA125 correlate with known high‐risk prognostic factors for endometrial cancer. Design Prospective multicenter study. Setting Three Danish tertiary gynecological oncology centers. Population A total of 352 patients with endometrial cancer and atypical endometrial hyperplasia consecutively referred between 1 September 2009 and 1 January 2012. Methods Preoperative blood samples were obtained from all patients. Biomarker levels were correlated with pathological characteristics of hysterectomy specimens. Main outcome measures FIGO stage, depth of myometrial invasion, cervical involvement, lymph node metastases, and histological type and grade of tumor. Results We found that both HE4 and CA125 were significantly positively correlated with histological grade (HE4: p = 0.002 and CA125: p = 0.027), lymph node metastases (HE4: p = 0.013 and CA125: p < 0.0001), myometrial invasion (p < 0.0001) and cervical involvement (p < 0.0001). Furthermore, a significant increase was found with increasing FIGO stage for both markers (p < 0.0001). In a combined index including age, the diagnostic value increases. Area under the receiver operating characteristics curves were higher for the index compared with the markers individually for all our endpoints. The calculated plots for the combined index may assist gynecologists in predicting the risk of deep myometrial invasion, cervical involvement and lymph node metastases. The analyses emphasize that the combined markers should be used in the prediction of prognostic factors. Conclusion This study confirmed that the markers are significantly elevated in patients with prognostic high‐risk factors and may, therefore, be used as an additional tool in combination with imaging and clinical information when planning the treatment of endometrial cancer patients.